1973
DOI: 10.1063/1.1679135
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation of CO by O atoms

Abstract: The vibrational relaxation of carbon monoxide by atomic oxygen has been measured behind incident shock waves in the temperature range of 1800–4000 °K. The atomic oxygen was produced by the rapid thermal decomposition of ozone. The experimentally derived relaxation times can be expressed in the form p τCO–O=exp(54 T−1/3−7.3) μsec·atm, which corresponds to a collisional probability of the order of 10−2 for the vibration-translation energy transfer. This is from two to three orders of magnitude larger than the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1974
1974
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 20 publications
0
23
0
1
Order By: Relevance
“…Models in the literature indicate that with only 1% H 2 O present, at the nozzle exit pressure and temperature, the vibrational relaxation time of N 2 is reduced to 5 µs (as opposed to many milliseconds), and this time is further reduced by increases in temperature or pressure. 20 Thus the observation of equilibrium in the combustion products is again plausible.…”
Section: Cars Resultsmentioning
confidence: 99%
“…Models in the literature indicate that with only 1% H 2 O present, at the nozzle exit pressure and temperature, the vibrational relaxation time of N 2 is reduced to 5 µs (as opposed to many milliseconds), and this time is further reduced by increases in temperature or pressure. 20 Thus the observation of equilibrium in the combustion products is again plausible.…”
Section: Cars Resultsmentioning
confidence: 99%
“…Center (1973) found O atoms an order of magnitude more efficient at relaxing the bending mode than Ar atoms; a probability of about 1~o was measured at 3000 K. Bass (1974) computed the probabilities assuming classical scattering with a hard sphere interaction and quasi-diatomic model for CO 2 for energies from 1 to 10 eV and found that when the C atom was struck by the impinging O atom, the average fraction of energy transferred to the v 2 mode was 0.447. Schatz and Redmon (1981) used quasi-classical trajectory theory to compute the cross sections for excitation of the bending mode and found avalueofl.9 x 10 -15 2 cm at 2.2 eV, whereas the excitation of the symmetric and asymmetric stretch modes were 2 and 4-5 orders of magnitude smaller, respectively.…”
Section: Ir Heating and 15-pm Coolingmentioning
confidence: 99%
“…During the Configuration C test campaign (with essentially identical CARS instrumentation to A) we acquired CARS data sets at the entrance plane with various levels of steam introduced in the facility heater. Since steam is known to greatly increase the rate at which N 2 relaxes to thermal equilibrium, 15 this experiment was expected to confirm the hypothesis that non-equilibrium was a result of processes in the flow and provide useful information on relaxation rates. Figure 4 shows experimental CARS spectra (200 shot averages) acquired near the center of the duct for cases with no steam (i.e., "clean air"), and 1.9%, 3.7% and 5.7% steam.…”
Section: A Existence Of Non-equilibriummentioning
confidence: 60%
“…Addition of steam was expected to bring the gas flow back towards equilibrium. 15 Computations of the flowfield for both equilibrium and thermal nonequilibrium have been performed and are compared with the data. Our contribution is to demonstrate that vibrational non-equilibrium can be found in supersonic nozzles as well as hypersonic nozzles, and show that published modeling methods can predict it.…”
Section: Introductionmentioning
confidence: 99%